2019
DOI: 10.1186/s41544-019-0039-4
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis and function of extracellular miRNAs

Abstract: Mature microRNAs (miRNAs) are 18-24-nucleotide non-coding RNAs with post-transcriptional regulatory functions and have been documented as an essential cornerstone of the genetic system. Although the traditional idea suggests that RNA molecules cannot be stable in extracellular environments due to ubiquitous ribonuclease, miRNA has now been verified as circulating in various body fluids in a stable, cell-free form. By associating with microvesicles (MVs) or RNA-binding proteins, extracellular miRNAs can be acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 62 publications
0
90
0
2
Order By: Relevance
“…RNA molecules have also been detected in extracellular fluids ( Figure 2 ). The origin of these molecules might be passive leakage from dead cells (e.g., linked to necrosis or apoptosis), or active secretion that might occur via membrane-bound vesicles (e.g., microvesicles) or follow a vesicle-free RNA-binding protein dependent pathway (e.g., with HDL, AGO2, NPM1 proteins) [ 2 , 67 ]. The latter mechanisms are thought to be well-regulated, energy-requiring processes.…”
Section: Cell-free Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…RNA molecules have also been detected in extracellular fluids ( Figure 2 ). The origin of these molecules might be passive leakage from dead cells (e.g., linked to necrosis or apoptosis), or active secretion that might occur via membrane-bound vesicles (e.g., microvesicles) or follow a vesicle-free RNA-binding protein dependent pathway (e.g., with HDL, AGO2, NPM1 proteins) [ 2 , 67 ]. The latter mechanisms are thought to be well-regulated, energy-requiring processes.…”
Section: Cell-free Rnamentioning
confidence: 99%
“…However, the biological significance of cf-RNAs is not well described yet. It is suggested that cf-RNAs might be involved in cell-to-cell communication and act as hormones [ 2 , 67 ]. These might affect tumor microenvironments contributing to tumor growth and invasion.…”
Section: Cell-free Rnamentioning
confidence: 99%
“…Subsequent studies have shown that MIR2911 also directly inhibits the replication of various viruses in addition to IAVs 3,4 . Upon dietary uptake, these microRNAs self-assemble into exosomes and are then secreted into the circulation and delivered into target tissues or specific cells, including the liver, lung, spleen, pancreas, and T cells [5][6][7] . Given the unique GC-enriched nucleotide composition of MIR2911 (GGCCGGGGGACGGACUGGGA) and after we analyzed the genome sequence of SARS-CoV-2, it is most likely that the virus genome contains MIR2911-binding sites and that MIR2911 can inhibit SARS-CoV-2 replication directly.…”
Section: O R R E S P O N D E N C E O P E N a C C E S Smentioning
confidence: 99%
“…Gestational Age (Weeks') We investigated plasma levels of the 21 miRNAs identified as both differentially and highly expressed in the matched placentas (Table 3). Whilst all 21 placental miRNAs were also detected in plasma, their origin is not necessarily placenta-specific, with cellular enrichment linked to various systemic compartments [28]. For example, five of these miRNAs have cellular enrichment in immune response, another three miRNAs in pluripotent and embryonic stem cells, and one miRNA is enriched in extra-embryonic stem cells.…”
Section: δ δmentioning
confidence: 99%